Pengembangan Kapasitas (Capacity Building) Kelembagaan pada Badan Kepegawaian Daerah Kabupaten Malang - Ratnasari, Jenivia Dwi (Jurnal Administrasi Publik, 2013)
Abstract : Institutional Capacity Building in the Regional Employment Agency Jombang. For service delivery to the community and increase regional competitiveness required capability or capacity of local governments adequate. Development of local government capacity always contains an understanding of the various efforts to improve the performance of services to the community. This study aims to describe and analyze the development of institutional capacity and supporting factors and obstacles encountered in the development of institutional capacity at the Regional Employment Board Jombang. This research uses descriptive study with a qualitative approach. The focus of the study include: (1) development of institutional capacity at the Regional Employment Board Jombang, (2) factors to be supporting and institutional capacity building. Results of this study was the development of institutional capacity in the Regional Employment Board Jombang is sufficient to supporting and inhibiting factors. Advice given is the Regional Employment Board Jombang be more innovative in the development of institutional capacity. Keywords: Capacity Building, Institutional. Abstrak : Pengembangan Kapasitas (Capacity Building) Kelembagaan pada Badan Kepegawaian Daerah Kabupaten Malang. Dalam rangka penyelenggaraan pelayanan kepada masyarakat dan peningkatan daya saing daerah diperlukan kemampuan atau kapasitas pemerintah daerah yang memadai. Pengembangan kapasitas pemerintah daerah senantiasa mengandung sebuah pemahaman tentang berbagai upaya meningkatkan kinerja pelayanan kepada masyarakat. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis pengembangan kapasitas kelembagaan dan faktor pendukung serta penghambat yang dihadapi dalam pengembangan kapasitas kelembagaan pada Badan Kepegawaian Daerah Kabupaten Jombang. Penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Fokus penelitian antara lain: (1) pengembangan kapasitas kelembagaan pada Badan Kepegawaian Daerah Kabupaten Jombang, (2) faktor-faktor yang menjadi pendukung dan penghambat pengembangan kapasitas kelembagaan. Hasil penelitian ini adalah pengembangan kapasitas kelembagaan yang ada di Badan Kepegawaian Daerah Kabupaten Jombang sudah cukup memadai dengan faktor pendukung dan penghambat. Saran yang diberikan adalah Badan Kepegawaian Daerah Kabupaten Jombang harus lebih inovatif dalam pengembangan kapasitas kelembagaan. Kata Kunci :Pengembangan Kapasitas, Kelembagaan.